Enjoying nature’s anti-aging wonders - Yadav, R K; Kalia, P (Indian Horticulture, 2019)
The regular consumption of dietary antioxidants or phytochemicals may reduce the risk of several serious diseases. These phytochemicals impart health benefits beyond basic nutrition. As vegetables contain a wide variety of biologically active, non-nutritive compounds known as phytochemicals, their regular consumption may help in reducing the risk of various diseases to a great extent. Green leafy vegetables are rich sources of vitamin A and C, mineral like calcium and iron and dietary fibres. They are low in carbohydrates and fat, and form a major category of vegetables that have been designated as 'nature's anti-aging wonders'.